IMPLEMENTATION OF A THEMATIC COMMUNITY SERVICE PROGRAM (KULIAH KERJA NYATA) IN SETIANEGARA VILLAGE, KUNINGAN REGENCY - Hasan Nur Faqih; Widya Farama Pantika; Dadan Taufik Fathurohman; Ary Kareliana; Cerina Salsabila; Adrian Fahrio; Reza Putra Jaya; Fa’iz Wijdan Awafa; Muhammad Luthfi Haidar Noor; Wahyu Hidayat; Rofiq Nurudin; Galang Rasyiq Suyudi; Putri Sindi Rinata; Zahra Aolia; Muhammad Fahmi Muzaki; Arif Putra Sundawa; Puza Zahratun Nisa; Nenik Triana; Ajeng Nanda Pitriani (Jurnal Abdisci, 2026)
Background: The Community Service Program (Kuliah Kerja Nyata/KKN) is an integral component of the Tri Dharma of Higher Education that encourages university students to actively engage in community empowerment through education, research, and public service. Aim: This article aims to describe the implementation of the Thematic KKN Program conducted by Group 17 of Universitas Swadaya Gunung Jati Cirebon in Setianegara Village, focusing on environmental, health, educational, legal, and information technology sectors. Methods: The program was implemented using educational, participatory, and collaborative approaches involving the village government, health workers, educational institutions, and the local community through main and supporting programs based on community needs. Results: The primary program, reforestation in the foothills of Mount Ciremai through tree-planting activities in strategic village areas, successfully increased public awareness of environmental conservation. Supporting programs such as school literacy movements, green school initiatives, integrated health service posts for toddlers, non-communicable disease monitoring, youth health services, home visits for disease screening, digital literacy education, blood type screening and donation activities, and the development of a village geographic information system enhanced community participation in health services, education, and technology utilization while providing more structured spatial village data. Conclusions: The implementation of the Thematic KKN Program made a significant contribution to improving community awareness and engagement in environment-based, health-oriented, and education-driven development. Implications: This program is expected to generate sustainable impacts on the community and serve as a multidisciplinary collaborative community service model for future KKN implementations.